Breaking Mechanism and Damage Evolution Rule of Ultra-High-Pressure Water Jet Impacting Steel Fiber Reinforced Concrete - Jialiang Liu; Yuelong Chen; Yujie Zhu (Advances in Civil Engineering)
Based on smooth particle hydrodynamics (SPH) method, this paper carried out the numerical simulation of ultra-high-pressure water jet (UHP-WJ) impacting steel fiber reinforced concrete (SFRC), verified the established numerical model by UHP-WJ impacting SFRC and computed tomography (CT) scanning experiments, and explored breaking mechanism and damage evolution rule of SFRC impacted by UHP-WJ. Results indicate that in the weak effect zone of steel fiber, the failure of concrete is generated and developed along the axial direction of UHP-WJ into a bowl-shaped crater with the combining action of compressive stress and shear stress. In the affected area of steel fiber, due to the inhomogeneity in the contact area of steel fiber and concrete, the stress concentration in the contact area is produced, causing the formation of propagated crack along the steel fiber. And the steel fiber has an obstruction effect on the development of broken bodies on the upper and lower sides of steel fiber. With the sustained action of UHP-WJ, the steel fiber in the intense radiation area of stress waves takes place fracture and finally the broken bodies on the upper and lower sides of steel fiber fuse. In addition, based on the CT scans and digital image processing technology, this paper also comparatively analyzed the internal fragmentations of SFRC and the ordinary concrete subjected to UHP-WJ impact, and it is found that compared with the ordinary concrete, there is smaller dimension of crater and it is difficult to engender macrocrack for SFRC, with lower damage and higher damage attenuation speed along the axial and radial directions.